Mathematical Thinking Skills and Their Relationship with Mathematical Beliefs of an Najah National UniversityStudents From Two Specializations: Mathematics And Teaching Methods Of Mathematics - Hadeel Salman Ali Odeh (My University, 2016)
This study aimed to determine the level of mathematical thinking skills and their relationship with mathematical beliefs of students in An-Najah national university from two specialties mathematics and teaching methods of mathematics. The study sample consisted of 220 students from the two specialties, mathematics and methods of teaching mathematics, at An-Najah National University, The participants in the sample were selected randomly, and the questionnaires were distributed in the second semester of the academic year 2015/2016. Two data collecting instruments were used in the study: mathematical thinking questions and a scale for measuring beliefs about mathematics, and validity and reliability tests were performed for each of the instruments. Independent T-tests،Anova and post-hoc Scheffé tests were used to answer the research questions. Pearson correlations were usedto find the relationships between mathematical thinking skills and mathematical beliefs. The study showed the following results: 1- There were statistically significant differences at (α ≤0.05) for all sub-scales of mathematical thinking skills and sub-scales of students' beliefs about mathematics between the students from the two specialties. 2- There were no statistically significant differences at (α ≤0.05) in the mathematical thinking skills and in the degree of students' beliefs attributed to gender 3- There were no statistically significant differences at (α ≤0.05) in students' beliefs attributed to the specialty، while there were statistically significant differences at (α ≤0.05) in mathematical thinking in favor of mathematics specialty students. 4- There were statistically significant differences at (α ≤0.05) between the sub-scales of mathematical thinking skills attributed to mathematics achievement in favor of students whose achievement (over 90%). At the same time, there were no statistically significant differences at (α ≤0.05) in the sub-scales of students' beliefs. 5- The relationships between the sub-scales of mathematical thinking and the sub-scales of attitudes towards mathematics wee statistically significant at (α ≤0.05). The study recommended focusing on the development of mathematical thinking skills in the mathematics curriculum. It also recommends instilling the mathematical concepts more accurately. In addition, teachers should develop the appropriate beliefs of mathematics students in order to have appropriate attitudes towards learning mathematics.

هدفت هذه الدراسة إلى معرفة مستوى مهارات التفكير الرياضي وعلاقتها بالمعتقدات نحو الرياضيات لدى طلبة جامعة النجاح الوطنية من التخصصين: الرياضيات وأساليب تدريس الرياضيات. تكونت عينة الدراسة من(220) طالباً وطالبة من تخصصي الرياضيات وأساليب تدريس الرياضيات في جامعة النجاح، حيث تم اختيار التخصصين بطريقة قصدية، واختيار الطلبة بطريقة عشوائية طبقية، وذلك في الفصل الدراسي الثاني من العام الدراسي (2015/2016م)، وتكونت أداة الدراسة من اختبار تفكير رياضي ومقياس لقياس المعتقدات نحو الرياضيات. وتحققت الباحثة من صدقهما وثباتهما بالطريقة المناسبة، ولتحقيق أهداف الدراسة استخدمت الباحثة اختبار (ت) للعينات المستقلة (t-test)، واختبار تحليل التباين الأحادي (One Way Anova)، واختبار الفروق البعدية (Scheffe’)، ومعامل ارتباط بيرسون لمعرفة العلاقة بين مهارات التفكير الرياضي ومعتقدات الطلبة نحو الرياضيات. أظهرت الدراسة النتائج التالية: -وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α≤0.05) لجميع مجالات مهارات التفكير الرياضي ومجالات اتجاهات الطلبة نحو الرياضيات وذلك بين الطلاب من التخصصين. - لا توجد فروق ذات دلالة احصائية عند مستوى الدلالة (α≤0.05) في مهارات التفكير الرياضي وفي درجة معتقدات الطلبة تعزى لمتغير الجنس. - لا توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (α≤0.05) لدرجة معتقدات الطلبة تعزى لمتغير التخصص، وتوجد فروق ذات دلالة إحصائية عند مستوى الدلالة (α ≤ 0.05) في مهارات التفكير الرياضي لصالح تخصص الرياضيات. - توجد فروق ذات دلالة احصائية عند مستوى الدلالة (α ≤0.05) بين مجالات مهارات التفكير الرياضي تعزى لمتغير التحصيل في الرياضيات لصالح الطلبة الذي تحصيلهم (أكثر من 90%)، و لا توجد فروق ذات دلالة إحصائية عند مستوى الدلالةα ≤0.05 )) في مستويات معتقدات الطلبة. - العلاقة بين مجالات التفكير الرياضي مع مجالات الاتجاهات نحو الرياضيات علاقة ذات دلالة إحصائية عند مستوى الدلالة. وأوصت الدراسة بضرورة تركيز مناهج الرياضيات على تنمية مهارات التفكير الرياضي، وغرس المفاهيم الرياضية بشكل أدق، وعلى المعلمين تنمية المعتقدات الصحيحة نحو الرياضيات لدى الطلبة لتكوين اتجاهات أكثر ايجابية لديهم نحو تعلم الرياضيات
مهارات التفكير الرياضي وعلاقتها بالمعتقدات نحو الرياضيات لدى طلبة جامعة النجاح الوطنية من التخصصين: الرياضيات وأساليب تدريس الرياضيات